Quantitative analysis of capsular microvasculature in relation to the thickness of chronic subdural hematoma - Jelenković, Boban; Nikolov, Vesna; Ilić, Jovan; Ilić, Marija; Marković, Aleksandar; Jocić, Hristina; Stojanović, Nikola; Pešić, Pavle (Vojnosanitetski pregled, 2026)
Background/Aim. Chronic subdural hematoma (CSDH) is an extra-axial, encapsulated, slow-growing hemorrhagic collection of blood, accompanied by local coagulopathy. This contributes to continuous re-bleeding from the newly formed capsule of hematoma, which leads to slow but progressive enlargement of the hematoma, with the potential to develop into a compressive intracranial lesion. The aim of this study was to investigate the relationship between the proliferation of sinusoid blood vessels and the growth and diameter of the CSDH. Methods. In this study, 33 cases of CSDH treated operatively were analyzed. A biopsy specimen (average size 3 × 3 mm) was obtained from the parietal capsule of the hematoma. The biopsied tissue samples were fixed in aqueous 4% buffered formaldehyde, routinely processed into paraffin-embedded slides, and immunohistochemically stained for the presence of the CD34 antigen. The profiles of microvascular bed blood vessels marked for CD34 were quantified, and the number of capillaries and sinusoids was expressed per one mm2. Results. The variables age and number of blood vessels showed a statistically significant association with the increase in hematoma volume (β = 0.422, p = 0.007; β = 0.486, p = 0.022, respectively). Older patients had a higher risk of enlarged hematoma volume, as did patients with a larger number of sinusoidal blood vessels. Conclusion. The number of sinusoids in the parietal capsule of CSDH per surface unit of 1 mm2 positively correlates with hematoma thickness, which emphasizes the importance of vascular theory in the development of a hematoma. Although CSDH is one of the most common neurosurgical diseases, its pathogenesis is still not fully understood. Further research in this field is necessary to develop potential new therapeutic options that would provide more comprehensive treatment modalities.